Common Cancers and Associated Risk Factors in Arua District Uganda - Angucia, Bridget Sharon (JOOUST, 2024)
Cancer is the second leading cause of mortality worldwide, with over 19 million cases and 10 million deaths worldwide. Approximately, 50% of all new cancer cases and 70% of all deaths occur in low-and middle-income countries. In Uganda, 34,008 new cancer cases were registered and 22,992 deaths occurred in 2020. Arua district was purposively selected for this study because no active cancer surveillance is done in the district and the findings of this research will help strengthen and evaluate cancer control interven tions in Arua. The goal of the study was to determine the common cancers and risk factors for the common lifestyle cancers amongst adult men and women in Arua. A retrospective cohort study, using medical records was used to determine the commonest cancers in Arua District for the period of 2017 to 2021. In addition, a nested case-control study was employed to investigate the cancer risk factors associated with the identified commonest cancers. Cases were identified from 5 health facilities in Arua and 1 in Kampala. Data was collected using a Data Abstraction Form and analyzed using Stata 17. The findings showed 1,118 new cancer cases were registered by this study, liver cancer was the commonest cancer in Arua accounting for 13.7%, followed by Cancer of the Cervix (11.8%), Breast (10.7%), Esophagus (10.5%) and Burkitt‟s lymphoma (6.4%). Men with a history of tobacco use were 3.2 times more likely to suffer from cancer of the esophagus than those with no history of tobacco use at 95% CI (1.7-5.9). Having more children was a protective factor against breast cancer in women, OR, CI (0.8, 0.7-0.9). The risk of getting breast cancer was 2.1 times higher in pre-menopausal women than post-menopausal women OR, CI (2.1, 1.2-3.7). A positive history of Contraceptive use increased the risk of breast cancer by 2.2 times, OR, CI (2.2, 1.0-4.7) in the bivariate analysis. In conclusion, this study suggested that cancer of the liver, cervix, breast, esophagus and burkitt lymphoma were the five top cancers in Arua and that reproductive risk factors came out strong for breast cancer while lifestyle risk factors came out strongly for cancer of the esophagus hence the need for targeted cancer control interventions against these cancers in Arua district.
Keywords: Common Cancers; Risk Factors; Uganda